William R. Day papers - Day, William R. (William Rufus), 1849-1923.
Correspondence, memoranda, minutes, reports, legal briefs, financial records, scrapbooks, printed matter, and other papers relating primarily to personal matters but also pertaining to his activities as U.S. secretary of state, U.S. Supreme Court justice, U.S. Court of Appeals (6th Circuit) judge, and president of the McKinley National Memorial Association. Subjects include foreign affairs, in particular relations with Spain; legal issues; political patronage requests; Day's affiliation with the Republican Party; and his relationship with William McKinley. Correspondents include Clara Barton; George B. Cortelyou; Charles W. Fairbanks; Mark Alonzo Hanna; Warren G. Harding; John Hay; William Randolph Hearst; Charles Evans Hughes; Henry Cabot Lodge; William McKinley; John Addison Porter; Theodore Roosevelt; Elihu Root; Robert Cecil, Marquess of Salisbury; William H. Taft; Joseph P. Tumulty; and Willis Van Devanter.
Lawyer, U.S. secretary of state, U.S. Supreme Court justice, and U.S. Court of Appeals judge.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barton, Clara, -- 1821-1912 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Fairbanks, Charles W. -- 1852-1918 -- Correspondence; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hearst, William Randolph, -- 1863-1951 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; McKinley, William, -- 1843-1901.; McKinley, William, -- 1843-1901 -- Correspondence; Porter, John Addison, -- 1856-1900 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Salisbury, Robert Cecil, -- Marquess of, -- 1830-1903 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; Van Devanter, Willis, -- 1859-1941 -- Correspondence; United States. -- Court of Appeals (6th Circuit); United States. -- Department of State; United States. -- Supreme Court; McKinley National Memorial Association; Republican Party (U.S. : 1854- ); Constitutional law -- United States; Law -- United States; Patronage, Political -- United States; Spain -- Foreign relations -- United States; United States -- Foreign relations -- 1897-1901.; United States -- Foreign relations -- Spain; United States -- Politics and government -- 1865-1933.; Cabinet officers; Jurists; Lawyers